Odpowiedź :
1.
[tex]\frac{x-1}{3x+6} = \frac{x+1}{x+2}\\(3x+6)(x+1)=(x-1)(x+2)\\3x^2+3x+6x+6=x^2+2x-x-2\\3x^2+9x+6=x^2+x-2\\3x^2-x^2+9x-x+6+2=0\\2x^2+8x+8=0\\2(x^2+4x+4)=0 /:2\\x^2+4x+4=0\\\Delta=4^2-4*1*4\\\Delta=16-16\\\Delta=0\\x_0=\frac{-4}2=-2[/tex]
2.
[tex]A=(-3, x)\\B=(y, 6)\\S=(-2,4)\\S=(\frac{x_1+x_2}2; \frac{y_1+y_2}2)\\-2=\frac{-3+y}{2} /*2\\-4=-3+y\\-4+3=y\\-1=y\\\\4=\frac{x+6}{2} /*2\\8=x+6\\8-6=x\\2=x[/tex]
3.
[tex]\frac{log_749+log_3\frac1{27}}{log_612-log_62} = \frac{2+(-3)}{log_6\frac{12}{6}}=\frac{2-3}{log_66}=\frac{-1}1=-1[/tex]